Solve $\mathrm{sin}\left(x\right)+\mathrm{cos}\left(x\right)=1$

eozoischgc
2021-12-13
Answered

Solve $\mathrm{sin}\left(x\right)+\mathrm{cos}\left(x\right)=1$

You can still ask an expert for help

Jeffery Autrey

Answered 2021-12-14
Author has **35** answers

Compare this equation to

And

Therefore,

Solutions:

Laura Worden

Answered 2021-12-15
Author has **45** answers

Use this identity

Use the identity

asked 2021-06-16

Airline passengers arrive randomly and independently at the passenger-screening facility at a major international airport. The mean arrival rate is 11 passengers per minute.

asked 2020-10-18

If $\mathrm{sin}x+\mathrm{sin}y=a{\textstyle \phantom{\rule{1em}{0ex}}}\text{and}{\textstyle \phantom{\rule{1em}{0ex}}}\mathrm{cos}x+\mathrm{cos}y=b$ then find $\mathrm{tan}(x-\frac{y}{2})$

asked 2021-09-02

Prove the identity

$\frac{1}{2\mathrm{csc}2x}={\mathrm{cos}}^{2}x\mathrm{tan}x$

Choose the sequence of steps below that verifies the identity

A)$\mathrm{cos}}^{2}x\mathrm{tan}x={\mathrm{cos}}^{2}x\frac{\mathrm{sin}x}{\mathrm{cos}x}=\mathrm{cos}x\mathrm{sin}x=\frac{\mathrm{sin}2x}{2}=\frac{1}{2\mathrm{csc}2x$

B)$\mathrm{cos}}^{2}x\mathrm{tan}x={\mathrm{cos}}^{2}x\frac{\mathrm{cos}x}{\mathrm{sin}x}=\mathrm{cos}x\mathrm{sin}x=\frac{\mathrm{sin}2x}{2}=\frac{1}{2\mathrm{csc}2x$

C)$\mathrm{cos}}^{2}x\mathrm{tan}x={\mathrm{cos}}^{2}x\frac{\mathrm{cos}x}{\mathrm{sin}x}=\mathrm{cos}x\mathrm{sin}x=2\mathrm{sin}2x=\frac{1}{2\mathrm{csc}2x$

D)$\mathrm{cos}}^{2}x\mathrm{tan}x={\mathrm{cos}}^{2}x\frac{\mathrm{sin}x}{\mathrm{cos}x}=\mathrm{cos}x\mathrm{sin}x=2\mathrm{sin}2x=\frac{1}{2\mathrm{csc}2x$

Choose the sequence of steps below that verifies the identity

A)

B)

C)

D)

asked 2022-01-17

Integral of

asked 2021-12-11

Verify the identity $\mathrm{sin}(A+\pi )=-\mathrm{sin}A$

asked 2021-09-12

Verify the identify.

$\frac{{\mathrm{tan}}^{2}\theta}{\mathrm{sec}\theta +1}=\frac{1-\mathrm{cos}x}{\mathrm{cos}x}$

asked 2021-09-14

Verify the identity:

$\frac{(\mathrm{cot}\left(\theta \right)+1)(\mathrm{cot}\left(\theta \right)+1)}{\mathrm{csc}\theta}=\mathrm{csc}\left(\theta \right)+2\mathrm{cos}\left(\theta \right)$